The association between arterial stiffness and cancer occurrence: Data from Kailuan cohort study - Jiang, Yinong; Xing, Aijun; Hidru, Tesfaldet Habtemariam; Li, Jiatian; Yang, Xiaolei; Chen, Shuohua; Xia, Yun-Long; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2023)
Background: This study aimed to investigate whether increased arterial stiffness, measured by brachial-ankle pulse wave velocity (baPWV) is associated with cancer. Methods: A total of 45627 Chinese adults underwent a baPWV examination. The participants were followed up from 1st January 2012 to 31th December 2018. Cox proportional hazards model was used to assess the association between the baPWV values and cancer. Results: During a total follow-up duration of 172775.69 person-years, there were 553 new cases of cancer. The subjects in the highest baPWV group showed an increased risk of cancer when compared with the lowest baPWV group as con-firmed by multivariate-adjusted hazard ratios (HR=1.51, 95% CI=1.14~2.00) in the entire cohort. Compared with participants in the lowest baPWV group, the HRs (95% CI) for digestive cancer in the second and third groups were 1.55 (1.00~2.40) and 1.99 (1.19~3.33), respectively. The Kaplan-Meier analysis demonstrated a significant increase in cancer in participants with a baPWV ≥18m/s (P <0.001). Compared with the lowest baPWV group, the highest baPWV group showed an increased risk of cancer in men (HR=1.72, 95% CI=1.22~2.43) and those <60 years (HR=1.75, 95% CI=1.20~2.55), respectively. Conclusions: Increased arterial stiffness measured by baPWV is associated with cancer occurrence, especially digestive cancer occurrence. Clinical Trial Registration: clinical trial number ChiCTR-TNRC-11001489